2019
DOI: 10.1016/j.ijppaw.2019.03.018
|View full text |Cite
|
Sign up to set email alerts
|

First reports of nasal and traumatic myiasis infection in endangered Przewalski's horses (Equus ferus przewalskii)

Abstract: Myiasis has great economic and medical importance. However, myiasis in wildlife that is caused by oestroid flies is relatively rarely recorded compared with that in humans and domestic animals. Recently, during our research on the conservation of Przewalski's horse (PH), we observed two new records of oestroid flies parasitizing wildlife in China. The first is the horse nasal bot fly, Rhinoestrus sp. (Diptera: Oestridae), found in a dead PH from Kalamaili Nature Reserve. One morphotype (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…So far, there is little research on traumatic myiasis in China and even less on traumatic myiasis in wild animals, but this disease has a serious impact on animal welfare and the economics of livestock breeding (Hall and Wall, 1995). At present, the main control strategies for myiasis are light trapping, conventional chemical control (Yan et al 2019), insecticidal applications, crutching, and so on (Hall, 1997). However, for the long-term health of captive animals, we should pay more attention to predicting…”
Section: Resultsmentioning
confidence: 99%
“…So far, there is little research on traumatic myiasis in China and even less on traumatic myiasis in wild animals, but this disease has a serious impact on animal welfare and the economics of livestock breeding (Hall and Wall, 1995). At present, the main control strategies for myiasis are light trapping, conventional chemical control (Yan et al 2019), insecticidal applications, crutching, and so on (Hall, 1997). However, for the long-term health of captive animals, we should pay more attention to predicting…”
Section: Resultsmentioning
confidence: 99%
“…Wild animals are also susceptible to myiasis due to wound infection by parasitic y larvae. For example, Huang et al [36] and Yan et al [37] found that Przewalski's Horse (Equus ferus przewalskii Poliakov, 1881) was highly susceptible to gastric myiasis in the Kalamaili Nature Reserve (KNR) and Xinjiang Research Centre for Breeding Przewalski's Horse, Xinjiang, China. A case of free-ranging eland (Taurotragus oryx) (Pallas, 1766) infected traumatic myiasis was reported from Kenya [38] In the 20th century, the musk deer (Moschus moschiferus) in the Sikhote-Alin Mountains found serious cutaneous myiasis caused by Booponus inexpectatus Grunin, 1947 (Diptera: Calliphoridae) forming subcutaneous warbles [39].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis and prevention of traumatic myiasis are extremely important because it seriously threatens the host health and causes signi cant economic losses to the livestock industry. The main control strategies for myiasis are light trapping and conventional chemical control at present [37]. For the long-term health of captive wild animals, we can use physical methods to prevent and control traumatic myiasis.…”
Section: Discussionmentioning
confidence: 99%
“…Oestrinae, Gasterophilinae, Hypodermatinae and Cuterebrinae (Robbins and Khachemoune, 2010;Francesconi and Lupi, 2012). The Oestrinae consists of four genera such as Oestrus, which cause myiasis in sheep, goat and man (Ahaduzzaman, 2019;Borade, 2019), Rhinoestrus which cause myiasis in donkey, Horse and man (Otranto et al, 2004;Yan et al, 2019), Cephenemyia which cause myiasis in Reindeer (Nilssen and Haugerud, 1995) and Cephalopina which cause myiasis in Camel (Basu and Charles, 2019). Genus Oestrus composed of eleven species, including O.…”
Section: Introductionmentioning
confidence: 99%